(untitled) (Revista de História da UEG (REVHIST), 2025)
This article is conducted by the problem of the correlation between History and literature, focusing on the analysis of a selection of fictional literary productions in regards, specifically, to the presence of the concept of the Christian God’s wrath as the primary cause of plague epidemics – to which a disciplinary attribute is given. In this sense, here it is taken into account the dynamics of transposition – to the literary sphere – of an ecclesiastical reference based on the thesis of the action of an angry God who punishes humanity based on its earthly behavior. As a result, the nuances of this aforementioned aspect are investigated in works produced at different times by authors coming from different origins, such as The Decameron, by the Italian Giovanni Boccaccio; A Journal of the Plague Year, by the British Daniel Defoe; and The Plague, by the French-Algerian Albert Camus. This research emphasizes, however, that it is very important for the historian to be cautious in the process of historical reading of fictional texts – so that their essential literary nature is conserved. Keywords: Divine wrath. Christian God. Epidemics. History and literature. Church.